2020
DOI: 10.1002/jrs.5940
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of Raman spectroscopy in the detection and diagnosis of oral cancer: A systematic review and meta‐analysis

Abstract: The aim of this study was to systematically review and assess the diagnostic accuracy of Raman spectroscopy (RS) for oral cancer tissue, oral precancerous lesions, and normal oral tissue. Methods: PubMed, Embase, Web of Science, the China National Knowledge Infrastructure, and gray literature were searched for all relevant articles published before July 2019. We used the Quality Assessment of Diagnostic Accuracy Studies tool to assess the quality of the included studies. We estimated the pooled sensitivity, sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
(277 reference statements)
1
8
0
Order By: Relevance
“…[17] Recent studies showed that Raman spectroscopy could be used to quantify biomarkers of kidney disease such as urea and creatinine in serum, [18] to quantify glucose and lipid components of serum, [19] and to quantify prostate-specific antigen values in serum of prostate cancer patients [20] aiming diagnosis. Very recently, two reviews thoroughly explore the potential of Raman spectroscopy for diagnosis of breast and oral cancers, [21,22] and a research paper proposed the detection of infectious diseases such as hepatitis B in plasma. [23] Recently, two reviews thoroughly explore the potential of Raman spectroscopy and others optical technologies in detecting viruses and prospect some applications for the detection of infectious diseases like COVID-19.…”
mentioning
confidence: 99%
“…[17] Recent studies showed that Raman spectroscopy could be used to quantify biomarkers of kidney disease such as urea and creatinine in serum, [18] to quantify glucose and lipid components of serum, [19] and to quantify prostate-specific antigen values in serum of prostate cancer patients [20] aiming diagnosis. Very recently, two reviews thoroughly explore the potential of Raman spectroscopy for diagnosis of breast and oral cancers, [21,22] and a research paper proposed the detection of infectious diseases such as hepatitis B in plasma. [23] Recently, two reviews thoroughly explore the potential of Raman spectroscopy and others optical technologies in detecting viruses and prospect some applications for the detection of infectious diseases like COVID-19.…”
mentioning
confidence: 99%
“…Yan et al was able to increase these numbers to the high 90s through implementation of a machine learning algorithm, albeit on a small dataset of only 12 patient samples 26 . A systematic review of using Raman for oral cancer diagnostics by Zhan, et al also describes a meta-analysis of 41 articles, citing that the accuracy of RS in oral cancer diagnostics on in vitro frozen tissues as 99.68% 25 . Although these are impressive numbers, the clinical relevance for diagnostics is lacking, as these studies do not address the need to create fast, non-invasive liquid biopsy approaches for rapid diagnostics.…”
Section: Discussionmentioning
confidence: 99%
“…It is suitable for studying the early diagnosis of oral cancer by distinguishing the different peaks contained in the Raman spectroscopy for qualitative studies. [9][10][11][12][13] Although Raman spectroscopy has been widely used in biomedical fields, the disadvantages of weak signal, low signal-to-noise ratio, and strong autofluorescence background have hindered its further clinical application. [14] The emergence of surface-enhanced Raman spectroscopy (SERS) has greatly overcome the shortcomings of conventional Raman spectroscopy and becomes a promising solution.…”
Section: Introductionmentioning
confidence: 99%